The HVEM-BTLA xxis restrains T cell help to germinal center B cells and functions as a cell-extrinsic suppressor in lymphomagenesis - Mintz, M; Felce, J; Chou, M; Mayya, V; Xu, Y; Shui, J; An, J; Li, Z; Marson, A; Okada, T; Ware, C; Kronenberg, M; et al. (Cell Press, 2019)
The tumor necrosis factor receptor superfamily member HVEM is one of the most frequently mutated surface proteins in germinal center (GC)-derived B cell lymphomas. We found that HVEM deficiency increased B cell competitiveness during pre-GC and GC responses. The immunoglobulin (Ig) superfamily protein BTLA regulated HVEM-expressing B cell responses independently of B-cell-intrinsic signaling via HVEM or BTLA. BTLA signaling into T cells through the phosphatase SHP1 reduced T cell receptor (TCR) signaling and preformed CD40 ligand mobilization to the immunological synapse, thus diminishing the help delivered to B cells. Moreover, T cell deficiency in BTLA cooperated with B cell Bcl-2 overexpression, leading to GC B cell outgrowth. These results establish that HVEM restrains the T helper signals delivered to B cells to influence GC selection outcomes, and they suggest that BTLA functions as a cell-extrinsic suppressor of GC B cell lymphomagenesis.